The energy expenditure of people with spinal cord injury while walking compared to an able bodied population. - Vosloo, Jana (My University, 2013)
Background and purposes of the study: In the field of spinal cord injury research there is an emphasis on the ability to ambulate as a functional outcome. With the tendency towards lower levels of physical activity in the SCI population it is of vital importance to facilitate any possible improvement in ambulation within this population. By having data of energy expenditure during a mobility assessment compared
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirement for the degree of Master of Science in Physiotherapy, Johannesburg, 2013